(untitled) (Baghdad Science Journal, 2009)
The aim of this work is to study the correlation between the electrons for Li atom in ground state through the calculation of the inter-particle distribution function f (r12) and inter-particle expectation values . By using the f(r12) function for KL shell in both singlet and triplet state .The Fermi hole have been evaluated .In this work the Hartree-Fock wave function (1993) have been used.